E KSPLORASI PILIHAN PENGGUNAAN LAHAN UNTUK PENINGKATAP EMBANGUNAN SEKTOR PERTANIAN (Studi Kasus di Kabupaten Jember, Provinsi Jawa Timur) - TEGUH HADI PRIYONO ; Prof. Candra Fajri Ananda, S.E., M.Sc, Ph.D.,Dr. Sasongko, S.E., M.S. ,David Kaluge, S.E., M.S., M.Ec-Dev., Ph.D
This study aims to analyze the land use to optimize rice production, employment, _x000D_ and income of farmers, as well as optimization of the three levels of achievement_x000D_ of these goals together. _x000D_ _x000D_ Sampling method used was purposive sampling, where the determination of _x000D_ respondents was selected from a farmer who had ? 0.5 ha of land. A Total of 18_x000D_ respondents were selected for each unit land. This has generated 1,116_x000D_ respondents were from 62 units.. LINDO program was used to analyze the land_x000D_ use in this study. _x000D_ _x000D_ The results showed that in rice production has not reached the optimal point, _x000D_ meaning that the amount of production can still be improved: a more modern_x000D_ farming, technology implementation, and post-harvest management are better. In_x000D_ terms of labor, the results indicated a small sensitivity level, and it showed that_x000D_ the additional labor will produce a smaller production. In addition, the income of_x000D_ farmers could still be improved in line with increase in production, stability of_x000D_ prices of agricultural products, and government policies that support the_x000D_ advancement of the agricultural sector. _x000D_ _x000D_ The implications of the results is that there is degree of saturation in the _x000D_ absorption of labor in the agricultural sector, particularly food crops. These_x000D_ conditions provide a warning to the government that the agricultural sector can_x000D_ not be expected as the support of labor employment. Some policies that could be_x000D_ done, are among others